Pemberdayaan Usaha Home Industry Sektor Informa - Ahmad, Abdul Chalid; Yetty, Yetty; Senuk, Abdurrahman; Suar, Abi (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
This dedication is to develop a people's economy which has an impact on improving the national economy without ignoring Indonesian economic democracy for MSME Partners in Toloa Village. The method used in this PKM activity is a participatory method where the community plays an active role in the process or flow of the program stages and its supervision. The achievement formulated by the PKM Team is that the PKM Program is able to provide a deep understanding of Partners, being able to develop business models and strategies in the form of managerial and management of financial reports and future business challenges.